Therapeutic Role of Astaxanthin and Resveratrol in an Experimental Rat Model of Supraceliac Aortic Ischemia-Reperfusion - Dilli, Dilek; Taşoğlu, İrfan; Sarı, Eyüp; Akduman, Hasan; Yumuşak, Nihat; Tümer, Naim Boran; Salar, Salih (American Journal of Perinatology, 2022)
Objective The aim of the study is to investigate the therapeutic effects of astaxanthin (AST) and resveratrol (RVT) on multiorgan damage in an animal model of the supraceliac aortic ischemia-reperfusion (I/R).Methods In this study, 28 rats (n = 7/group), 200 to 250 g in weight, were randomized to four groups (1: Sham, 2: Control + I/R, 3: AST + I/R, and 4: RVT + I/R). Following the abdominal incision, aortic dissection was performed in the sham group without injury. Other groups underwent I/R injury via supraceliac aortic clamping (20 minutes) and reperfusion. The rats were administered olive oil (3 mL/kg) orally for 2 weeks before and 1 week after the laparotomy. Additionally, oral AST (10 mg/kg) or RVT (50 mg/kg) was given to the study groups. All rats were sacrificed on the 3rd week of the experiment after blood samples were taken for analysis. Multiple rat tissues were removed.Results We found that RVT increased total antioxidant status (TAS) and superoxide dismutase (SOD) levels, and decreased total oxidant status (TOS), oxidative stress index (OSI), myeloperoxidase (MPO), and malondialdehyde (MDA) levels, while AST increased the levels of TAS, decreased TNF-α, MDA, TOS, and OSI (p <0.05). Pathological investigations of the rat tissues revealed that both AST and RVT ameliorated tissue damage and apoptosis.Conclusion Our study suggests that AST and RVT might show therapeutic effects against oxidative tissue damage and apoptosis in an animal model of aortic I/R. Further studies are required.Key Points
Keywords: antioxidants; aorta; ischemia/reperfusion; rat